The timing of cognitive aid access during simulated pediatric intraoperative critical events. Issue 6 (22nd April 2020) - Clebone, Anna; Watkins, Scott C.; Tung, Avery
Abstract: Background: Many cognitive aids are formatted in a step‐by‐step fashion with the intent that the aid will be accessed at the beginning of a critical event and that key behaviors will be performed in sequence. Aims: We hypothesized that, during simulated pediatric intraoperative critical events, anesthesia clinicians may not use cognitive aids immediately after the onset of a critical event but instead access the aid only after first performing several key behaviors. Materials and Methods: This manuscript is a re‐analysis of previously published simulation data. The original study involved 89 clinicians participating in 143 pediatric intraoperative events divided into 6 types: arrhythmia, venous air embolus, hypoxemia, malignant hyperthermia, hypotension, and supraventricular tachycardia. For each trial involving cognitive aid use, we measured the time from event trigger to cognitive aid use, and the number and type of key behaviors performed by simulation participants prior to cognitive aid access. Results: Cognitive aid use was sought in 66 of 93 trials where it was available. Sufficient data for this analysis were available in 65 trials. The average time from event trigger to first cognitive aid use was 258 seconds. In 62/65 trials (95%), the cognitive aid was accessed after at least one key behavior had already been performed. The time from event trigger to cognitive aid use varied by type of scenario ( P  = .03, df 5, adjusted H 12.78), with the shortest time for "supraventricular tachycardia" (90 [66, 156] seconds (median [IQR]) and the longest time for "hypoxemia" (354 [192, 492] seconds). Conclusion: In simulated critical events, anesthesia residents and student nurse anesthetists often consulted a cognitive aid only after first performing at least some key behaviors. Incorporating the possibility of delayed access into critical event cognitive aid design may facilitate the effectiveness of that aid.